2010
DOI: 10.5194/sg-5-11-2010
|View full text |Cite
|
Sign up to set email alerts
|

"Doing with space": towards a pragmatics of space

Abstract: This article intends to explore the conditions of possibility of a pragmatics of space. How are practices constructed through space? How are the different ways of practising places are informed by different aspects of spatial dimensions? In order to get into this question, three points are developed. Firstly we will delimit the field of what is termed here "pragmatics" as larger than "pragmatism", with reference to recent developments within French sociology. Secondly we will propose a shift from geographies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 32 publications
0
20
0
6
Order By: Relevance
“…Any deciphering of the urban context is more enriched by considering the relationship between affectivities or emotions and corporeity than by considering emotions in themselves. And in this respect it is worth remembering the approach of Merleau-Ponty (1962), who observed that things (the world external to the human being) are embodied within us by our perception. They are not therefore a pure perceived object -external and recognized -but are rooted in our body, articulated to the very structure of our perception.…”
Section: Incorporated and Territorializing Affectivitymentioning
confidence: 99%
“…Any deciphering of the urban context is more enriched by considering the relationship between affectivities or emotions and corporeity than by considering emotions in themselves. And in this respect it is worth remembering the approach of Merleau-Ponty (1962), who observed that things (the world external to the human being) are embodied within us by our perception. They are not therefore a pure perceived object -external and recognized -but are rooted in our body, articulated to the very structure of our perception.…”
Section: Incorporated and Territorializing Affectivitymentioning
confidence: 99%
“…À travers la description et l'explicitation des mécanismes qui président à l'organisation de quelques spatialités périurbaines appréhendées à l'échelle individuelle, il s'agissait bien de poser un premier jalon pour potentiellement apporter un certain nombre de pistes susceptibles de répondre à cet objectif qui sous-tendait la recherche Périvia : celui du ménagement des territoires de vie périurbains pour la réalisation de leur durabilité. L'ensemble de ces choix épistémologiques, éclairant notre démarche, explique le cheminement qui a été le nôtre dans cette recherche, partant de l'observation, de la description fine d'un ensemble de cas particuliers, pour tendre progressivement vers la compréhension des conditions de réalisation des modes d'habiter périurbains, des manières socialement partagées de « faire avec l'espace » (Lussault et Stock, 2010) et avec le mouvement (Terrhabmobile, 2013).…”
Section: La Mobilité Du Côté Des Individusunclassified
“…Schatzki (1991) provides a more philosophical rationale for the perspective, relying heavily on the work of Heidegger. For a more "pragmatic" view of social space, see Lussault and Stock (2009). 7.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%